Approximation of solution problem in laser melting simulation - Третяк, Валерія Анатоліївна (Technology audit and production reserves, 2012)
The article deals with approximation problem arising while partial differential equation solving using finite difference method with adaptive mesh refinement. The comparison of Lagrange polynomial interpolation and rational curves approximation is performed. An adaptive method of weight evaluation is suggested